Promoting mind-body health in schools : interventions for mental health professionals - Maykel, Cheryl; Bray, Melissa A., 1964- (Applying psychology in the schools book series., 2020)
"This book discusses how to improve students' mental and physical well-being by implementing various mind-body interventions in schools. Following a three-tiered service delivery model, it provides guidelines for applying these practices universally, with small groups, and with individuals. Chapters review the benefits, limitations, and potential risks associated specific mind-body practices, including yoga, mindfulness, biofeedback, and expressive therapy. They also address how to target specific problems, such as eating and sleep disorders, chronic pain, and trauma"--